Nurse Turnover: Implication on Health Care Delivery - Bisnar, Joyce C.; Pegarro, Kathleya Grace N. (JPAIR Multidisciplinary Research, 2018)
Nurse turnover is a major problem to all health care organizations because of its strong effects on client outcomes, motivation to work, job dissatisfaction and provision of quality patient care. The study aimed to determine the implication/ effects of nurse's turnover on healthcare delivery. Mixed method and Descriptive research design were employed, and the census was used in the selection of the participants. A validated self- made questionnaire, focus group discussion and key informant interview was utilized to gather the empirical data required. The study revealed that there was a decrease nurse turnover rate in the government hospital and an increase in private hospitals due to low salary, no/ less fringe benefits, poor/no health insurance coverage, better benefits and compensation package offered by other hospitals/countries and lower patient ratio. However, with the increase or decrease in the turnover rate, health care delivery in relation to the identified five (5) key areas of nurses' responsibility are still affected due to increased nurse-client ratio, interpersonal relationship, stressful environment and attitudes of the millennial nurses. Further, the majority of the participants are millennials and they outnumbered the generation X and baby boomers who created a generation gap in terms of health care delivery. This shift in attitude poses a great challenge for hospitals to retain millennials because they are growing in numbers and are replacing baby boomers and generation X. Thus, hospitals had to learn, adjust and develop management strategies to accommodate and understand the unique style and attitudes of the millennials for retention.
Keywords: Nursing; nurse turnover; push and pull factor; descriptive design; Cotabato City; Philippines